Heterogeneous reactions of gaseous hydrogen peroxide on pristine and acidic gas-processed calcium carbonate particles: effects of relative humidity and surface coverage of coating - Y. Zhao; Chen, Z. M.; X.L. Shen; D. Huang (Atmospheric Environment, 2013)
Atmospheric aging appears to alter physical and chemical properties of mineral dust aerosol and thus its role as reactive surface in the troposphere. Yet, previous studies in the atmosphere have mainly focused on the pristine surfaces of mineral dust aerosol, and the reactivity of aged mineral dust toward atmospheric trace gases is poorly recognized. This work presents the first laboratory investigation of heterogeneous reactions of gaseous hydrogen peroxide (H2O2), an important atmospheric oxidant, on the surfaces of HNO3 and SO2-processed calcium carbonate particles as surrogates of atmospheric mineral dust aged by acidic trace gases. It is found that the processing of the calcium carbonate particles with HNO3 and SO2 has a strong impact on their reactivity toward H2O2. On HNO3-processed particles, the presence of nitrate acts to either decrease or increase H2O2 uptake, greatly depending on RH and surface coverage of nitrate. On SO2-processed particles, the presence of surface sulfite appears to enhance the intrinsic reactivity of the mineral particles due to its affinity for H2O2, and the uptake of H2O2 increases significantly relative to the pristine particles, in particular at high RH. The mechanisms for heterogeneous reactions of H2O2 with these processed particles are discussed, as well as their potential implications on tropospheric chemistry. The results of our study suggest that the reactivity of mineral dust aerosol toward H2O2 and maybe other trace gases is markedly dependent on the chemical composition and coverage of the coatings as well as ambient RH, and thus will vary considerably in different polluted air masses.